Modeling faults of quadcopter aerial vehicle using petri nets - Abreu López, Ailet; Izaguirre Castellanos, Eduardo; Abreu García, José Rafael; Bravo Cortes, Julio César (My University, 2019)
The development of models focused on the detection and diagnosis of failures in autonomous aerial vehicles, constitutes a novel subject, where for this application context the complexity of the algorithms and sensorial systems on board of these vehicles constitutes a challenge. In this field Petri Networks are used as a tool for fault detection given the facilities they provide for the modeling of complex systems in terms of their graphic representation and offering a simple solution. In this investigation a fault model is developed that allows the detection of faults based on Petri Nets applied to an air vehicle type Quadcopter, this model allows to determine the possible existence of off-line faults for this type of aerial vehicle, through the analysis of the data coming from the flight controller and measurements of the sensors on board. It is shown that the model satisfies the properties established for the verification of models with Petri Nets using two of the methods; reachability tree and state equation
Keywords: Modeling; Petri Nets; Aerial Vehicles; Fault Detection